Donald P. Warwick, Bitter Pills, Population Policies & Their Implementation in eight developing countries, Cambridge University Press, 1983, 229 p. - García y Garma, Irma Olaya (Estudios Demográficos y Urbanos, 1984)
DONALD P. WARWICK, BITTER PILLS, Population Policies & Their Implementation in eight developing countries, Cambridge University Press, 1983.